PENERAPAN METODE PEMBELAJARAN PLAY BASED LEARNING DENGAN MEDIA PUZZLE DALAM MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN SD - Neftihana; Iis Aprinawati; Nurhaswinda; Rizki Ananda; Molli Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students' early reading skills through the Play Based Learning method with the help of Puzzle media in class I students of UPT SDN 004 Sungai Jalau in the 2024/2025 Academic Year. The type of research used is Classroom Action Research. The subjects of this study were students, while the objects in this study were the Play Based Learning method with Puzzle media and students' early reading skills. This study was carried out in 2 cycles, each cycle was carried out in 2 meetings. Data collection techniques used in this study were observation, tests and documentation. Based on the increase in the number of students who achieved the learning objective achievement criteria (KKTP) and the increase in the average class and classical scores. The classical completeness presentation value in cycle 1 meeting 1 was 61.90%, in cycle I meeting II 76.19%, and cycle II meeting 1 90.47%, in cycle II meeting II 95.23%. Based on the results of the study, it can be concluded that through the Play Based Learning method with the help of Puzzle media, it can improve students' early reading skills in class I UPT SDN 004 Sungai Jalau.